Anal Fissure - Beaty, Jennifer Sam; Shashidharan, M. (Clinics in Colon and Rectal Surgery, 2016)
Anal fissure (fissure-in-ano) is a very common anorectal condition. The exact etiology of this condition is debated; however, there is a clear association with elevated internal anal sphincter pressures. Though hard bowel movements are implicated in fissure etiology, they are not universally present in patients with anal fissures. Half of all patients with fissures heal with nonoperative management such as high fiber diet, sitz baths, and pharmacological agents. When nonoperative management fails, surgical treatment with lateral internal sphincterotomy has a high success rate. In this chapter, we will review the symptoms, pathophysiology, and management of anal fissures.
Keywords: anal fissure; sphincterotomy; anal pain